Short Communication: The role of microbial rhizosphere in enhancing plant growth of Jatropha curcas in soil contaminated mercury - WIWIK EKYASTUTI; HANNA ARTUTI EKAMAWANTI (Biodiversitas Journal of Biological Diversity, 2018)
Ekyastuti W, Ekamawanti HA. 2018. Short Communication: The role of microbial rhizosphere in enhancing plant growth of Jatropha curcas in soil contaminated mercury. Biodiversitas 19:  701-705. Soil in the area of ex-gold mining, has the chemical-physical constraints to the growth of plants. These chemical-physical constraints are low organic matter, poor of nutrient, acid pH, very low CEC, soil texture dominated by sand, and mercury contamination. This area needs to be rehabilitated. Previous research has found that Jatropha curcas as a plant tolerant to mercury. On the other hand, some types of microbial rhizosphere such as arbuscular mycorrhizal fungi (AMF) and mercury reducing bacteria (MRB) also have an ability to reduce mercury. The purpose of this study was to determine the role of microbial components of AMF and MRB in enhancing the growth of J. curcas in tailings contaminated mercury. The study was conducted in two places, in the greenhouse and in the tailing area of ex-gold mining, using factorial completely randomized design. Results showed that interactions between AMF and MRB were simultaneously able to enhance the growth of J. curcas not only in the greenhouse, but also in the field (tailing area). In the greenhouse (nursery), several isolates of Bacillus sp, Bacillus sp + Glomus SS11 and Bacillus sp + Glomus SS18 in the forms of inoculum were very effective in enhancing the seedling growth of J. curcas. However, results were apparently changed after those seedlings were planted in the field (tailings of ex-gold mining). The combination of Bacillus sp. + Glomus SS18 was the best treatment to enhance the growth of J. curcas of all used treatments. This result proves that the role of microbial rhizosphere, especially AMF and MRB, could effectively enhance the growth of J. curcas in tailings contaminated with mercury.